The killing hills [large type] - Offutt, Chris, 1958- (Offutt, Chris, 1958- Mick Hardin novels., 2023)
"Mick Hardin, a combat veteran now working as an Army CID agent, is home on a leave that is almost done. His wife is about to give birth, but they aren't getting along. His sister, newly risen to sheriff, has just landed her first murder case, and local politicians are pushing for city police or the FBI to take the case. Are they convinced she can't handle it, or is there something else at work? She calls on Mick, who is well-suited to staying under the radar. As he delves into the investigation, he dodges his commanding officer's increasingly urgent calls while attempting to head off further murders" --